ANALISIS KUALITAS PELAYANAN PUBLIK DI KANTOR KELURAHAN TONDO KOTA PALU SULAWESI TENGAH - Siti Nur Aziza; Friscia Novianti Setiawan; Indah Amalia; I Wayan Indrawan; Mustainah Mustainah; Intam Kurnia; Dandan Haryono (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Public service is an activity carried out to meet the needs of the community and residets in acchordance with laws and regulation such as those in Law No.25 off 2009 concerning public serice witch states date the state is obliged to serve every citizen to fulfill their basic rights and needs. The purpose of this study is to fine out aboute the quality of public services in the Tondo Village Office Mantikulore Distric, Palu City,Central Sulawesi Province,whether it is in racchordnce with the privision of laws adan regulatiions. Data is analyzed using qualitative research meet hods to determine the quality of public services. In data collection, the methods used are observation,intervius and questinnairies. Based on the results of the study,it can be conceluded that the quality of public services in the Tondo Village Office, Mantikulore Districht, Palu City,Centra Sulawesi Province has been running very well in providing services to the community, hoever,in terms of facilities and infrastructure,its still does not meet th service needs in the village office.